2018
DOI: 10.14202/vetworld.2018.42-47
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of selected viral pathogens in pigs reared in organized farms of Meghalaya from 2014 to 16

Abstract: Aim:A pilot study was carried out to find out the seroprevalence of Porcine circovirus 2 (PCV2), classical swine fever virus (CSFV), and Porcine respiratory and reproductive syndrome virus (PRRS) in pig population of Meghalaya.Materials and Methods:Serum samples were collected from piglets of 40–45 days age group, growers, and sows reared under organized and unorganized management in 11 districts of Meghalaya situated in the Khasi, Jaintia, and Garo hills divisions in the time period of 2014-2016 from apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In this study, the overall prevalence of CSFV antibodies detected was 40.71% (Table 2) which was comparatively less when compared to previous pan India surveillance finding of 594 serum samples from 12 states and 287 tissue samples tested from 13 states of India using commercial ELISA kits in which mean prevalence of CSFV antibodies in suspected sera was 63.3% and CSFV antigen in the suspected samples was 76.7% (Nandi et al, 2011). The present study is in corroboration with the earlier study where 45.15% seroprevalence was detected (Mukherjee et al, 2018) but higher than reported by earlier worker, i.e., 37% (Patil et al, 2018). The study revealed the endemicity of the diseases in Mizoram since majority of the samples were collected from apparently healthy and suspected animals.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, the overall prevalence of CSFV antibodies detected was 40.71% (Table 2) which was comparatively less when compared to previous pan India surveillance finding of 594 serum samples from 12 states and 287 tissue samples tested from 13 states of India using commercial ELISA kits in which mean prevalence of CSFV antibodies in suspected sera was 63.3% and CSFV antigen in the suspected samples was 76.7% (Nandi et al, 2011). The present study is in corroboration with the earlier study where 45.15% seroprevalence was detected (Mukherjee et al, 2018) but higher than reported by earlier worker, i.e., 37% (Patil et al, 2018). The study revealed the endemicity of the diseases in Mizoram since majority of the samples were collected from apparently healthy and suspected animals.…”
Section: Introductionsupporting
confidence: 85%
“…This implies that swine population acts as a major carrier of viruses and thus plays an important role in its dissemination. Harboring these viral pathogens without showing any distinguishable symptoms, these animals may be considered as reservoir host as viremia is prolonged and most infections are subclinical (Mukherjee et al, 2018). In the present study, Kolasib districts of Mizoram has shown the highest prevalence (54.1%) of CSFV antibodies compared to Aizawl (45%), Champhai (23.2%) and Serchhip (42.7%) districts as shown in Fig.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Co-infection of PCV2 with other pathogens has been reported [19][20][21][22][23]. We also examined if PCV3 was concurrent with major diarrheal viruses ( Table 3).…”
Section: Co-infections Of Pcv3 With Other Swine Viral Pathogensmentioning
confidence: 99%
“…The OD 450nm values of these samples were from 0.11 to 1.72, and the PCV3 DNA copies varied from 10 2.03 to 10 5. 19 . Fig.…”
Section: Comparison Of Pcv3 Detection By Qpcr and Indirect Elisa In Pmentioning
confidence: 99%